Numerical Investigation of the Seismic Behavior of Unanchored Steel Tanks with an emphasis on the Uplift Phenomenon - Jalal Akbari; Omid Salami; Mohsen Isari (Fracture and Structural Integrity)
Ground steel storage tanks are widely used in different industries. Regarding the significance of these structures, ensuring the proper performance of such structures in earthquakes needs evaluating their seismic performance. The present study examines the seismic behavior of an unanchored fluid storage system via ABAQUS after validation with an experimental model. Next, the uplift of the bottom sheet is studied using the accelerogram records of the 1940 El Centro and 1994 Northridge earthquakes. The overturning moment time history of the fluid storage system and the maximum overturning moments were obtained to identify their behavior. The results indicated that not bracing storage tanks leads to the uplift phenomenon. Finally, the maximum axial stress of the storage tank shell was compared with the values recommended in the design codes to control the buckling.